CODE-SWITCHING AND SLANG USED BY GEN Z INDONESIANS ON SOCIAL MEDIA - Aprilia Bernike Kandiawan (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2023)
Most social media active users are Gen Z Indonesians Gen Z, who usually communicate with others on social media by switching their code to another code or language and using slang. The switchover from Bahasa Indonesia to other regional dialects or English and the use of slang have been dominated on social media, not limited to words but also sentences. This study observes and examines the reasons that underlying Indonesians Gen Z perform code-switching and use slang, as well as the advantages and disadvantages that will arise. The research method used is descriptive qualitative research. Data were collected from journals, reports, or books that had been written by other researchers and analyzed by content or document analysis and discourse analysis. This research found that there are some reasons, such as social reasons, convenience, referential functions like emphasizing the precise message, and affective functions, also there are three advantages and a disadvantage of code-switching and using slang in communication in social media.